Ecological studies on parasitic copepods infecting fish fins, with special references to the life cycle and infection-site specificity - Norshida Ismail
Parasitology is the science that deals with one of the several different kinds of symbiotic relationships including the parasitism (Bush et al. 2001). Organism involves in parasitism are called parasite and the host (Rohde, 1993). Bush et al. (2001) picked the definition of parasites according to the Oxford English Dictionary as the organism, which lives in or upon another organism and draw it nutrient directly from it. While, host is an organism that harbors a parasite, or a mutual or commensal symbiont, typically providing nourishment and shelter (Rohde, 1993). To define parasitism, one has to emphasize the damage parasites inflicted on hosts, the metabolic dependence of parasites on hosts, and ecological interactions between populations of these two species of living organisms (Bush et al. 2001). Ecology has been defined as the study of interactions between organisms and their environments and among the organisms inhabiting these environments (Sobecka, 2012). This is a complex field of study, which is why it should be investigated on various levels. In the ecology of parasites, the niche which is the entirety of the parasite-host relationship and fragmentation, is of fundamental importance (Combes, 1995). Parasite lives at the expense of the host, but it is also dependent on its host in many other aspects. Parasite may impose many impacts to the host. the nutritional, habitat, and dispersal exploitation of a parasite may lower the fitness of the host. They also have the ability to modify host behavior that may lead to their castration (Levri, 1998). Based on the way of invasion to a host, parasite can be classified into several categories. Endoparasite is the parasite confined within the body of the host while ectoparasite is typically restricted to the exterior part of the host's body (Sobecka, 2012). Mesoparasites are the in between group, with some part of the parasite buried into the host tissue, and some part is exposed to the outdoor world (Kearn, 2010). All parasitic nematodes and the majority of flatworms are endoparasites, while the majority of arthropods are ectoparasites.